Current Study of the Detection and Treatment Targets of Spinal Tuberculosis - Wang, Biao; Gao, Wenjie; Hao, Dingjun (Current Drug Targets, 2020)
Spinal tuberculosis is a common manifestation of extrapulmonary tuberculosis and osteoarticular tuberculosis. Common clinical manifestations include constitutional symptoms, back pain, spinal tenderness, paraplegia, and spinal deformities. They are the common causes of paralysis and could increase the mortality in patients. Most cases of spinal tuberculosis remaining undiagnosed, and early clinical symptoms and imaging manifestations lack specificity, which explained the reason why it is difficult to identify from atypical spinal metastases, brucellosis and other diseases. The rate of missed diagnosis and misdiagnosis for spinal tuberculosis is high. If spinal tuberculosis diagnostic targets could be early detected, the therapeutic targets can be effectively treated, which can not only control the progress of the disease and shorten the course of treatment, but also reduce the economic pressure and avoid spinal deformity. Therefore, early diagnosis should be our focus. Comprehensive use of a variety of diagnostic targets can improve the early diagnosis rate of spinal tuberculosis. Here, we review the progress of laboratory, imaging and gene detection in the diagnosis of spinal tuberculosis in recent years.
Keywords: spinal deformity